(untitled) (Studia Prawnicze / The Legal Studies, 1975)
Układ RFN z NRD był jednym z elementów tzw. wschodniej polityki rządu RFN, sprzyjającej odprężeniu i regulacji stosunków politycznych w Europie. Wniosek Rządu Bawarskiego uzależniał realizacje układu od orzeczenia Związkowego Trybunału Konstytucyjnego, ponieważ Trybunał, zgodnie z art. 93 pkt 1 ust. 2 ustawy zasadniczej był kompetentny do oceny zgodności układu z konstytucją i władny uznać go za nieważny, a tym samym wyłączyć go z systemu obowiązującego prawa. Artykuł składa się z dwóch części. Pierwsza ujmuje prawne podstawy działalności Związkowego Trybunału Konstytutycjnego, właściwość rzeczową, skład, organizacje, postępowanie oraz moc wiążąca jego orzeczeń. Część druga zawiera naalizę funkcji, jakie wypełnia Trybunał w systemie prawa i konstytucyjnym ustroju państwa. Przy analizie tak podstaw prawnych działalności Trybunału, jak i jego funkcji w konstytucyjnym ustroju RFN, posłużono się metodą prawno-dogmatyczną, bez szerszego odwołania się do orzecznictwa Trybunału. Germany’s agreement with the GDR was one of the elements of the German government’s so-called Eastern policy, which favoured relaxation and regulation of political relations in Europe. The Bavarian Government’s proposal made the implementation of the treaty conditional on a ruling by the Federal Constitutional Court, since the Court, in accordance with Article 93(1)(2) of the Basic Law, was competent to assess the constitutionality of the treaty and had the power to declare it invalid and thus exclude it from the system of applicable law. The article consists of two parts. The first captures the legal foundations of the Federal Constitutional Court, the substantive jurisdiction, composition, organisation, proceedings and the binding force of its decisions. The second part contains an analysis of the functions the Court performs in the legal system and the constitutional system of the state. In analysing both the legal basis of the Court’s activities and its functions in the constitutional system of Germany, a legal-dogmatic method was used, without extensive reference to the Court’s case law.